Satisfacción del socio y posicionamiento en la Cooperativa de Ahorro y Crédito LTDA mi Financiera, Iquitos, 2019 - Caballero Cárdenas, Andre Kenso (2021)
The objective of the research was to determine the relationship between the satisfaction of the member and the positioning in the Savings and Credit Cooperative My Financial the Iquitos, in the year 2019. The research design was correlational, and had as a population to 688 members and a sample of 246 members. The survey technique was used for data collection. The results obtained with respect to the variable customer satisfaction of the Savings and Credit Cooperative My Financial the Iquitos, in 2019, was valued by respondents: 79.7% said they had high satisfaction, 6.1% satisfaction average and 14.2% low satisfaction. Regarding the variable Positioning of the Savings and Credit Cooperative My Financial the Iquitos, in the year 2019, 70.7% perceive the Positioning of the Cooperative as very good, 17.9% as good and 5.7 as bad or very bad. The main conclusion was that there is a statistically significant relationship between the Satisfaction of the member and the Positioning of the Savings and Credit Cooperative My Financial the de Iquitos, in the year 2019, demonstrated by the Chi Square test in which it showed that the P-value = 0.000 less than the 0.05 level of significance assumed for the investigation.